Vulvar Myiasis in Early Pregnancy - Jha, Rajani; Upadhyaya, Indira; Thapa, M; Awal, R (Nepal Journal of Obstetrics and Gynaecology, 2016)
Myiasis is a parasitic infestation caused by the larvae of several fly species in various body wound and orifices. Vulvar myiasis is an extremely rare location. This is a case report of a 25 years old pregnant lady who presented with signs of burning sensation, itching and irritation invulval area. Vulval inspection revealed an ulcer on mons pubis with induration and tiny maggots crawling over the ulcer. She was managed conservatively with daily dressing and manual removal of larva along with vaseline gauge packing and application of topical antimicrobials as well as prophylactic systemic antibiotics. The wound was left to heal by secondary intention. Patientwas discharged after seven days of hospital stay with advice on personal hygiene to avoid reinfection.